Etika Profesi dan Aspek Pidana dalam Pelayanan Kesehatan: Harmonisasi menurut Undang-Undang No. 17 Tahun 2023 tentang Kesehatan - Abdullah, Mariyam; Binarsa , Deka Bagus (Syntax Literate, 2025)
Health services are the main pillar in the fulfillment of Human Rights in the health sector. Health workers are not only required to have medical competence, but also must uphold professional ethics in their practice. On the other hand, the complexity of health services opens up the potential for violations that have an impact on criminal liability. This research aims to examine the position of professional ethics, the regulation of criminal aspects, and the form of harmonization between the two in health services based on Law No. 17 of 2023 concerning Health. The research method used is juridical-normative with legislative, conceptual, and case study approaches. The results of the study show that professional ethics are the moral foundation in health services, while criminal law plays a role as an instrument of protection for patients. Law No. 17 of 2023 tries to harmonize the two by emphasizing legal protection for health workers who work according to professional standards, as well as regulating the mechanism for resolving violations in stages ranging from ethical, discipline, to criminal. This harmonization is important to create a health service system that is fair, professional, and oriented towards the protection of all parties. This study recommends strengthening the role of professional ethics institutions and increasing legal understanding for health workers and law enforcement officials to avoid disproportionate criminalization.